Implementasi Media Sosial Instagram sebagai Strategi Komunikasi Korporat PLN Icon Plus - Gusvandi Harki; Vivien Febri Astuti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The digital transformation era compels corporations to shift their communication paradigms from one-way dissemination to interactive engagement. This study aims to analyze the use of Instagram as a corporate communication strategy for PLN Icon Plus in building brand awareness, utilizing Luttrell's Circular Model of SOME and Aaker's Brand Awareness Pyramid. Employing a descriptive qualitative approach, data were gathered through in-depth interviews with the Manager of Corporate Communication & CSR, staff journalists, and visual designers, complemented by systematic observations of the @pln.iconplus Instagram account. The results indicate that PLN Icon Plus has applied the SOME cycle in a structured manner: the Share and Manage stages are executed through rigorous agenda-setting and account consolidation; the Optimize stage involves hook strategies and digital identity visualization; and the Engage stage is realized through personalized interaction and complaint channeling. A key finding reveals that within the B2B corporate communication context, organic views are considered more significant than conventional engagement metrics. This conclusion is derived from Instagram Insights data, which demonstrates a broader strategic reach among stakeholders, further validated by informant justifications regarding the priority of corporate narrative dissemination. Theoretically, this study proves that disciplined social media management is a primary determinant in elevating a brand's position toward top of mind.